HUBUNGAN ANTARA PENGETAHUAN DAN TINDAKAN DOKTER GIGI DALAM UPAYA PENCEGAHAN PENYAKIT MENULAR - Annisa Meirani Hidayat; Kusuma Arbianti; Erdianto Setya Wardhana (Faculty of Dentistry, Universitas Islam Sultan Agung, 2016)
Background: Infectious disease is a disease caused by a particular toxin.Infectious diseases that acquired from the hospital environment called nosocomial infections. Hepatitis B, tuberculosis, and HIV/AIDS is a commonly infectious disease that often found in dental practice. The risk for dentist to infected the infectious diseases are very high, due to direct contact with saliva. The awareness of infection control at the dentist is very important to prevent disease transmission.This aim of this research is to determine the relationship between the level of knowledge of the dentist with the precautions against infection diseases.Method: Cross-sectional analytic study with one group post-test only design was done in 25 dentists in the Dental Hospital Sultan Agung Semarang. The instrument for this research was used a questionnaire and a check list. Questionnaire was used to determine the level of knowledge, while the check list to determine the actions of the respondents. Data were analyzed with Pearson Correlation Test.Result: The questionnaire and the check list that was used is valid and reliable. The results showed 95.8% of respondents have a good knowledge, 4.2% are good enough knowledgeand 0% is lackingknowledge. All respondents have a good action in the prevention of infectious diseases. Pearson correlation test results showed p = 0.041, which means that there is a relationship between the level of knowledge of the dentists with the precautions against infectious diseases.Conclusion: It can be concluded that there is a relationship between the level of knowledge of the dentists with the precautions of infectious diseases, where the strength of the correlation is moderate.